2014
DOI: 10.3389/fnagi.2014.00188
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Homeostasis in Duchenne Muscular Dystrophy: Modulating Autophagy as a Promising Therapeutic Strategy

Abstract: Muscular dystrophies are a group of genetic and heterogeneous neuromuscular disorders characterized by the primary wasting of skeletal muscle. In Duchenne muscular dystrophy (DMD), the most severe form of these diseases, the mutations in the dystrophin gene lead to muscle weakness and wasting, exhaustion of muscular regenerative capacity, and chronic local inflammation leading to substitution of myofibers by connective and adipose tissue. DMD patients suffer from continuous and progressive skeletal muscle dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 73 publications
2
49
0
3
Order By: Relevance
“…This is a critical step in recruiting mitochondria destined for autophagy to nascent autophagosomes. Abnormalities in lysosomal function and autophagy have been linked to several forms of muscle injury and myopathy, including muscular dystrophy (46)(47)(48)(49). How deficits in mitophagy or macroautophagy in general lead to muscle injury and rhabdomyolysis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical step in recruiting mitochondria destined for autophagy to nascent autophagosomes. Abnormalities in lysosomal function and autophagy have been linked to several forms of muscle injury and myopathy, including muscular dystrophy (46)(47)(48)(49). How deficits in mitophagy or macroautophagy in general lead to muscle injury and rhabdomyolysis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lack of dystrophin, the progressive decline in the autophagy process has been recently highlighted as one of the main causes of the inefficient function of satellite cells during DMD progression (Fiacco et al, ). These results, in agreement with previous findings, suggested that autophagy represents a promising target for the treatment of DMD (Sandri et al, ; De Palma et al, ; Fiacco et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out concerning PI3K/Akt impairment in the mdx mouse as well as in DMD in humans. Activation of Akt has been found to be higher in the mdx mouse (6,9) and also in DMD patients (10). As Akt plays a major role in cell signalling, its impairment leads to various defects in downstream protein signalling, including cell proliferation, differentiation, apoptosis, autophagy and protein synthesis perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is defective in mdx mice (16) and DMD humans (17). Restoration of beclin1 levels in Col6a1 -/animals and long-term exposure to a low-protein diet (9,13) can reactivate autophagy and partly ameliorate the dystrophic features/phenotype. Col6a1 -/animals display an impairment of basal autophagy, which determines the persistence of dysfunctional organelles in muscle fibres leading to muscle degeneration (13).…”
Section: Introductionmentioning
confidence: 99%